2016
DOI: 10.1515/ejnm-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of nano- and ultrafine Ni particles to synthetic biological solutions: predicting fate-related dissolution and accumulation

Abstract: The growing production and use of nickel (Ni) nanopowders with low biopersistence makes dissolution and accumulation degree in a body an important parameters needed for the risk assessment of nanoparticles. We propose an experimental approach for rapid determination of the dissolution degree of nanoscale (77 nm) and ultrafine (275 nm) Ni particles in synthetic biological solutions. It has been shown that after 2 h of exposure to simulating saliva and lysosomal liquid the dissolution degree of nanoparticles can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In contrary, platinum as a noble metal is ‘not soluble’ in water (Artelt et al 1999). Furthermore, Abzhanova et al (2016) reported high dissolution rates for nickel particles in biological simulants. After 2 h of exposure to artificial saliva or lysosomal liquid, dissolution rates of up to 30 respectively 60% were recorded.…”
Section: Introductionmentioning
confidence: 99%
“…In contrary, platinum as a noble metal is ‘not soluble’ in water (Artelt et al 1999). Furthermore, Abzhanova et al (2016) reported high dissolution rates for nickel particles in biological simulants. After 2 h of exposure to artificial saliva or lysosomal liquid, dissolution rates of up to 30 respectively 60% were recorded.…”
Section: Introductionmentioning
confidence: 99%